2006
DOI: 10.1016/j.ejpain.2005.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Psycho‐social factors and coping strategies as predictors of chronic evolution and quality of life in patients with low back pain: A prospective study

Abstract: Besides somatic factors, psychosocial predictors of LBP chronic evolution may be identified. Both aspects must be taken into account in order to prevent chronic pain. Perhaps cognitive-behavior therapy may help LBP patients to cope with pain in a better way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
13

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(79 citation statements)
references
References 69 publications
(92 reference statements)
4
62
0
13
Order By: Relevance
“…Conversely, the repeated experience of lack of control over aversive events may result in helplessness (10). In line with this, several studies have found that a perceived lack of control is associated with unfavourable outcomes in chronic pain conditions (11,12).…”
Section: Introductionmentioning
confidence: 52%
“…Conversely, the repeated experience of lack of control over aversive events may result in helplessness (10). In line with this, several studies have found that a perceived lack of control is associated with unfavourable outcomes in chronic pain conditions (11,12).…”
Section: Introductionmentioning
confidence: 52%
“…Participants point to the position on the line between the faces to indicate how much pain they are currently feeling [30].…”
Section: Visual Analog Scale Pain Scorementioning
confidence: 99%
“…Thereby, cognitive factors seem to particularly mediate the relationship of pain with functional and emotional adjustment [8,20,40].…”
mentioning
confidence: 99%